Most Christian American religious leaders silently believe in climate change, and informing their congregation can help open dialogue - Stylianos Syropoulos; Gregg Sparkman (Proceedings of the National Academy of Sciences, 2025)
Religious leaders shape the attitudes and beliefs of their congregations. In a nationally representative sample of U.S. religious leaders ( N = 1,600), the majority of which were of a Christian faith, we find that nearly 90% believe in anthropogenic climate change to some degree. From this 90%, a total of 60% believe humans play a major role and an additional 30% believe they play a role, but a more minor one. Yet roughly half have never discussed it with their congregation, and only a quarter have mentioned it more than once or twice. In a sample of Christian Americans representative of the proportions of major national denominations ( N = 987), we find that Christians underestimate the prevalence of their leaders who believe in climate change by 39 to 45 percentage points. Conversely, having a religious leader who talks about climate change predicts greater willingness to discuss it with fellow churchgoers and attend climate events. In an experimental intervention on another sample matching major Christian American denomination ( N = 959), we find that providing the actual consensus level of religious leaders’ belief in climate change reduces congregants’ misperception of religious leaders, increases their perception that other church members believe in and are open to discussing climate change, and leads Christians to believe that taking climate action is consistent with their church’s values while voting for politicians who will not take climate action is not.